Valuation Mechanisms of Fine European Tapestries in the International Auction Market - Radermecker, Anne-Sophie (FormAkademisk, 2023)
Using textile arts (fine European tapestries) as a case study, we demonstrate the potential of hedonic regression to better understand buyers’ willingness to pay for these works at auction. Once highly valued, this medium offers unique characteristics that differ in part from paintings and affect buyers’ purchasing behaviors differently. Based on a dataset of 602 wall-hangings sold at Christie’s and Sotheby’s over the last decade, our empirical findings suggest that local place branding, aesthetics (antiqueness, ornamental effects), and material quality are crucial price determinants of textile arts.